2018
DOI: 10.1186/s41938-018-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of wilt-nematode complex infecting gerbera by Bacillus subtilis under protected cultivation

Abstract: A strong antibiotic producer, Bacillus subtilis strain Bbv 57 (KF718836), has been utilized for the management of wiltnematode complex (Fusarium oxysporum f. sp. gerberae, Meloidogyne incognita) in gerbera under greenhouse conditions in the Department of Floriculture, Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu, India. The strain strongly inhibited F. oxysporum f. sp. gerberae (KM523669) mycelial growth to an extent of 44.33 and 63.33%, at 10 and 100 μl, of culture filtrate, respectively. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…The lipopeptides might be most related to the surfactin family of the lipopeptides. Similar results were obtained by Ramyabharathi and co-authors on Bacillus subtilis Bbv57 producing surfactin and iturin, which were confirmed on TLC with Rf value of 0.3 for surfactin and 0.7 for iturin family while comparing with the standard (Sigma-Aldrich) [35]. Likewise, Yánez-Mendizábal and co-workers reported surfactin and iturin with Rf values 0.3 and 0.7 respectively [36].…”
Section: Product Characterizationsupporting
confidence: 82%
“…The lipopeptides might be most related to the surfactin family of the lipopeptides. Similar results were obtained by Ramyabharathi and co-authors on Bacillus subtilis Bbv57 producing surfactin and iturin, which were confirmed on TLC with Rf value of 0.3 for surfactin and 0.7 for iturin family while comparing with the standard (Sigma-Aldrich) [35]. Likewise, Yánez-Mendizábal and co-workers reported surfactin and iturin with Rf values 0.3 and 0.7 respectively [36].…”
Section: Product Characterizationsupporting
confidence: 82%
“…The presence of the lipopeptides, surfactin and iturin was confirmed (Ramyabharathi et al . ). Likewise, Adam et al .…”
Section: Biological Control Based On Bacillus Speciesmentioning
confidence: 97%
“…; Ramyabharathi et al . ). However, such studies are often speculative or fail to elaborate on how the secondary metabolites were detected or distinguished from primary metabolites.…”
Section: Using Metabolomics To Detect Possible Nematicidal Compoundsmentioning
confidence: 97%
See 2 more Smart Citations